2016
DOI: 10.4236/ars.2016.51003
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Vegetation Cover on the Oh Soil Moisture Retrieval Model: A Case Study of the Malinda Wetland, Tanzania

Abstract: Soil moisture is an important parameter that drives agriculture, climate and hydrological systems. In addition, retrieval of soil moisture is important in the analysis as well as its influence on these systems. Radar imagery is best suited for this retrieval due to its all-weather capability and independence from solar irradiation. Soil moisture retrieval was done for the Malinda Wetland, Tanza

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Detailed descriptions of each texture measure can be obtained in Haralick (1979). We searched for local precipitation data near our study site, given that humidity has an influence on backscatter values (Kirimi et al 2016). The meteorological stations closest to our study site were Porto Velho (code A925 113 Kilometers away) and Ariquemes (code A940, 80 km away).…”
Section: Sentinel Data Acquisition and Processingmentioning
confidence: 99%
“…Detailed descriptions of each texture measure can be obtained in Haralick (1979). We searched for local precipitation data near our study site, given that humidity has an influence on backscatter values (Kirimi et al 2016). The meteorological stations closest to our study site were Porto Velho (code A925 113 Kilometers away) and Ariquemes (code A940, 80 km away).…”
Section: Sentinel Data Acquisition and Processingmentioning
confidence: 99%
“…As for semi-empirical or empirical models, they are often difficult to apply to sites other than those on which they were developed and are generally valid only for specific soil conditions. The empirical models are often favored by users because the models are easier to implement and invert [1][2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies have demonstrated the necessity to eliminate the effects of vegetation on soil moisture retrieval [71]. It was discovered that soil moisture retrieval is much more accurate when vegetation cover is considered [72]. To further explore the backscatter coefficients derived in Section 4.3 with different vegetation descriptors, the soil moisture was retrieved from the backscatter to allow comparison of observed soil moisture in the oil palm study area.…”
Section: Vegetation Effects On Soil Moisture Retrieval Based On Polarizationmentioning
confidence: 99%